Is a regional credit rating agency for the ASEAN feasible? - Tullao, Tereso S., Jr. (Animo Repository, 2018)
In the spirit of deepening the bond markets of the ASEAN+3 region, as well as addressing the inadequacies put forth by the underrating of bonds by global credit rating agencies (GCRAs) and their lack of recognition of domestic CRAs’ (DCRAs) ratings, we look into the feasibility of a regional CRA (RCRA). Establishing an RCRA is faced with hurdles related to institutional and reputational constraints, mechanisms of information exchange, compatibility of financial reports, operational limitations, governance structure, and regulatory frameworks. In this light, we provide a brief discussion on potential alternatives such as the credit ratings initiative of the National University of Singapore (NUS), mutual recognition agreements, recognition of DCRAs’ ratings, removing the sovereign cap, regional GCRA ratings, cooperation between DCRAs and GCRAs, and the harmonization among DCRAs.